POTENSI KORIDOR JALAN YOS SUDARSO SEBAGAI RUANG TERBUKA DAN LANSEKAP KOTA PALANGKA RAYA - Noor Hamidah, Mahdi Santoso (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT One of important place in historic city of Palangka Raya is a big public open space along the corridor of Yos Sudarso Street where various activities found here. Besides sport and social activities conducted in this place, many street vendors also arrised as well as green open space utilization. This paper is conducted to find out the potentiality of Yos Sudarso corridor to be optimilized as public open space and important landscape in Palangka Raya by applying a concept approach research. The concept of public open space and landscape possible to come out by implementing a planning concept of open space and re-arrange informal sector location and completing infrastructures such as garbage management , lighting system, and street vendor stall design . Finally, a potential concept of green space need to balancing between vegetation and the presence of public building requirement to achieve sustainable development and to reduce global warming impacts. Key words: Potential open space, landscape, Palangkaraya